Investigating the non-work antecedents of workplace deviance - Waqas Farooq; Omar Khalid Bhatti; Rabeea Ishaq; Sadaf Kashif (Cogent Business & Management, 2023)
Deviance in the workplace, which has a huge destructive and harmful impact on the organization, is of key concern to academicians and practitioners. Existing literature focuses on the work-related antecedents of workplace deviance. However, the non-work-related antecedents have received little attention. Hence, the present research attempts to understand, the non-work antecedents that aggravate deviant behavior among employees at a workplace. The Gioia qualitative research approach was used to understand, examine, analyze, and interpret the views of respondents. A semi-structured interviewing technique was adopted. The respondents were encouraged to share their own experiences, thoughts, and understanding regarding the phenomenon. A sample of 25 experienced respondents from public and private organisations in Pakistan were interviewed. The results indicate that commuting factors (road hindrances, conflict behaviors, traffic discipline, and over-speeding), social factors (family-work conflict, and disturbed social relations), and an individual's lifestyle (attitude, physical inactivity, and sleep deprivation) are the contributing factors pertaining to the non-work antecedents of workplace deviance. The current study contributes to the literature by focusing on the non-work antecedents of workplace deviance.
Keywords: 650; commuting; disturbed social relations; family; sleep deprivation; traffic; unhealthy lifestyle; Workplace deviance